DESKRIPSI JUMLAH LIMFOSIT ABSOLUT PADA HIPERURISEMIA - Meri Meri; Yane Liswanti; Hemarisa Nurizkillah (Journal of Indonesian Medical Laboratory and Science, 2020)
Hyperuricemia is a condition of increased levels of uric acid in the blood. Physiological conditions, uric acid has the form of a solute. The crystals will form if the levels are above 6.8 mg/dL or at the saturation point. It will settle in various tissues, including the kidneys and joints. Hyperuricemia can cause various types of diseases such as hypertension, kidney disorders, arterosklesrosis, cardiovascular, gout and others. Crystals monosodium urat cancause innate and adaptive immune responses. Innate immune response is played by macrophages for phagocytic and produce pro-inflammatory cytokines and can stimulate lymphocyte activation. Its presence can be determined by counting the absolute lymphocyte count, thus giving an indication of the prognosis of the disease due to hyperuricemia. The purpose of this research is to describe the absolute lymphocyte count in hyperuricemia. This type of research is descriptive cross sectional study approach. The number of research subjects was 30 participants taken by purposive sampling with criteria for men aged 18-65 years, hyperuricemia, fasting 10-12 hours, no obesity, no infection, not children and not elderly. The results showed that 6.7% (2 people) had an increased absolute lymphocyte count, and 93.3% (28 people) had a normal absolute lymphocyte count. In conclusion, absolute lymphocyte counts can describe the prognosis due to hyperuricemia, as a result of the adaptive immune response.